Poly Cystic Ovarian Syndrome and Treatment - Utman, Naeema; Ruby, Nasreen (Journal of Postgraduate Medical Institute, 2011)
Polycystic ovary syndrome is a condition characterized by disruption of the regular process leading to anovulation and associated hyperandrogenemia, noraml or elevated level of oestrogen, raised LH level and abnormal FSH: LEH ratio.